The Basis of Constitutional Adjudication in Germany - Nge Nge Aung (Universitas Lampung, 2022)
The Federal Constitutional Court of Germany leads the judiciary’s independence by protecting human rights within the Basic Law’s legal framework. In this case, the jurisdiction of the Court is essential to analyse comprehensively. The first and foremost function is interpretation. It is concerned with the extent of a supreme federal authority’s rights and duties and the citizens who can enjoy the fundamental rights under the Basic Law. The rest are abstract judicial review, constitutional complaint, and concrete judicial review. These all seem to depend on the Court’s interpretation and the supremacy of human dignity. Therefore, the issues lie when human dignity becomes a constitutional principle to resolve economic, social, and political disputes within the constitutional framework both in Germany and the European Union in practice. This research will used qualitative approach method. According to the literature reviews, human dignity is supreme, but it does not mean absolute.